Isolation, Characterization, and Drug Sensitivity of Mycobacterium tuberculosis in Captive Sloth Bears (Melursus ursinus): Unnatural Habitat With Human Environment May Predispose Sloth Bears to Tuberculosis - Marinaik, Chandranaik B.; Sha, Arun A.; Manjunatha, Venkataravanappa; Shylaja, S.; Rathnamma, Doddamane; Rizwan, Apsana; Nagaraja, K. (Frontiers in Veterinary Science, 2022)
We describe the isolation, molecular characterization, and drug sensitivity of Mycobacterium tuberculosis recovered from lung tissues of four rescued captive sloth bears (Melursus ursinus) at Bannerghatta Biological Park (BBP), Bangalore, India. These bears had lived most of their life with humans in circus companies. They were rescued and housed in the Bear Rescue Center (BRC) of BBP. Upon rescue, they showed signs of unthriftiness, chronic debility, and failed to respond to symptomatic treatments. Over the period of the next 12–14 months, the four sloth bears died and the post-mortem examination revealed nodular lesions in the lungs that showed the presence of acid-fast bacilli. Polymerase chain reaction (PCR), culture, and nucleotide sequencing confirmed the bacilli as Mycobacterium tuberculosis. Histopathology of the lungs revealed characteristic granulomatous reaction with caseation. We determined the sensitivity of these isolates to rifampicin and isoniazid drugs by a WHO approved test, Line Probe Assay (LPA) using Genotype MTBDRplus VER 2.0. We discuss the role of unnatural habitat with the human environment in predisposing captive sloth bears for tuberculosis (TB). In the absence of any other reliable ante-mortem diagnostic test, this study recommends the use of LPA for early detection of TB in captive wild animals, which will help in taking necessary steps to prevent its further spread to animal caretakers and other susceptible animals in captivity.